2019
DOI: 10.2147/ijn.s219820
|View full text |Cite
|
Sign up to set email alerts
|

<p>Co-Administration Of iRGD Enhances Tumor-Targeted Delivery And Anti-Tumor Effects Of Paclitaxel-Loaded PLGA Nanoparticles For Colorectal Cancer Treatment</p>

Abstract: BackgroundNanoparticles exhibit great promise for improving the solubility and tissue-specific distribution of chemotherapeutic agents; however, the passive and highly variable enhanced permeability and retention (EPR) effects observed in tumors frequently leads to insufficient delivery of nanodrugs into tumors. The tumor-penetrating peptide iRGD can actively enhance tumor-selective delivery of nanoparticles into tumors by binding to integrin and interacting with tissue-penetrating receptor neuropilin-1.Materi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 59 publications
(20 citation statements)
references
References 48 publications
1
19
0
Order By: Relevance
“…Next, the HepG2 cells were incubated with DMEM, MIL-101(Fe)@sor NPs, and MIL-101(Fe)@sor NPs + iRGD for 6 h (using 10 ÎŒM Sor and 30 ÎŒmol/L iRGD). 24 Then the cells were collected, washed with PBS three times, centrifuged, and uniformly dispersed in agarose gel. Finally, the cells were scanned with 3.0 T MR, and the T2* mapping image signals were reconstructed using a GE AW 4.6 Advantage Workstation.…”
Section: Methodsmentioning
confidence: 99%
“…Next, the HepG2 cells were incubated with DMEM, MIL-101(Fe)@sor NPs, and MIL-101(Fe)@sor NPs + iRGD for 6 h (using 10 ÎŒM Sor and 30 ÎŒmol/L iRGD). 24 Then the cells were collected, washed with PBS three times, centrifuged, and uniformly dispersed in agarose gel. Finally, the cells were scanned with 3.0 T MR, and the T2* mapping image signals were reconstructed using a GE AW 4.6 Advantage Workstation.…”
Section: Methodsmentioning
confidence: 99%
“…Some studies investigated whether the co-administration of iRGD with drug delivery systems can improve chemotherapeutic efficacy. For example, Zhong et al showed that the co-administration of iRGD with the paclitaxel-loaded poly (lactic-co-glycolic acid) (PLGA) nanoparticle facilitates drug accumulation in tumors, and improves the antitumor effects when compared with the paclitaxel-loaded PLGA without iRGD co-administration [ 129 ]. The co-administration of iRGD with irinotecan-loaded silicasome was also reported to activate the NRP-1-mediated transcytosis transport pathway in pancreatic ductal adenocarcinoma, supporting the notion that iRGD can improve the efficacy of irinotecan-based silicasome [ 131 ].…”
Section: Applications Of Irgd In Cancer Therapymentioning
confidence: 99%
“…Poly (lactic-co-glycolic acid) (PLGA) has been one of the most studied polymeric carriers approved by the FDA for anticancer therapy because of its low systemic toxicity and high biodegradability compared to other polymeric systems. 7 As a controlled-release formulation of drugs, 8 drug molecules in NPs are slowly released from the pores of the material surface as the PLGA degrades, as a result, the drugs maintain a constant concentration for a long time, prolong the exposure time, and improve the bioavailability. 9 What is more, another attractive characteristic of PLGA over other nanoparticles is that PLGA is one of the best characterized biodegradable copolymers because it decomposes into nontoxic lactic acid and glycolic acid and further into H 2 O and CO 2 eliminated from the body with low to no toxicity.…”
Section: Introductionmentioning
confidence: 99%